Answer
The correct answer is C. (12, -1).
Step-by-step
I will solve the system of equation using the substitution method. I will solve for x in the second equation and then substitute that value in for x in the first equation.
x - 2y = 14
x + 3y = 9
Part 1: Solve for x in the second equation
x + 3y = 9
x + 3y - 3y = 9 - 3y
x = 9 - 3y
x = -3y + 9
Part 2: Substitute -3y + 9 in for x in the first equation and solve for y
x - 2y = 14
(-3y + 9) - 2y = 14
-5y + 9 = 14
-5y + 9 - 9 = 14 - 9
-5y = 5
-5y / -5 = 5 / -5
y = -1
Part 3: Use the value for y to solve for x in the second equation
x = -3y + 9
x = -3(-1) + 9
x = 3 + 9
x = 12
Part 4: Write your answer as a coordinate with x and y values
x = 12; y = -1
(12, -1)